Co-Occurrence of Post-Intensive Care Syndrome Problems Among 406 Survivors of Critical Illness*. Issue 9 (September 2018) - Marra, Annachiara; Pandharipande, Pratik P.; Girard, Timothy D.; Patel, Mayur B.; Hughes, Christopher G.; Jackson, James C.; Thompson, Jennifer L.; Chandrasekhar, Rameela; Ely, Eugene Wesley; Brummel, Nathan E.
Abstract : Objectives: To describe the frequency of co-occurring newly acquired cognitive impairment, disability in activities of daily livings, and depression among survivors of a critical illness and to evaluate predictors of being free of post-intensive care syndrome problems. Design: Prospective cohort study. Setting: Medical and surgical ICUs from five U.S. centers. Patients: Patients with respiratory failure or shock, excluding those with preexisting cognitive impairment or disability in activities of daily livings. Interventions: None. Measurements and Main Results: At 3 and 12 months after hospital discharge, we assessed patients for cognitive impairment, disability, and depression. We categorized patients into eight groups reflecting combinations of cognitive, disability, and mental health problems. Using multivariable logistic regression, we modeled the association between age, education, frailty, durations of mechanical ventilation, delirium, and severe sepsis with the odds of being post-intensive care syndrome free. We analyzed 406 patients with a median age of 61 years and an Acute Physiology and Chronic Health Evaluation II of 23. At 3 and 12 months, one or more post-intensive care syndrome problems were present in 64% and 56%, respectively. Nevertheless, co-occurring post-intensive care syndrome problems (i.e., in two or more domains) were present in 25% at 3 months and 21% at 12 months. Post-intensive care syndrome problems in all three domains were present in only 6% at 3 months and 4% at 12 months. More years of education was associated with greater odds of being post-intensive care syndrome free ( p < 0.001 at 3 and 12 mo). More severe frailty was associated with lower odds of being post-intensive care syndrome free ( p = 0.005 at 3 mo and p = 0.048 at 12 mo). Conclusions: In this multicenter cohort study, one or more post-intensive care syndrome problems were present in the majority of survivors, but co-occurring problems were present in only one out of four. Education was protective from post-intensive care syndrome problems and frailty predictive of the development of post-intensive care syndrome problems. Future studies are needed to understand better the heterogeneous subtypes of post-intensive care syndrome and to identify modifiable risk factors. Abstract : Supplemental Digital Content is available in the text.